Effect of working pressure on Sn/In composition and optoelectronic properties of ITO films prepared by high power impulse magnetron sputtering. (February 2022) - Zhao, Ming-Jie; Zhang, Jin-Fa; Huang, Qi-Hui; Wu, Wan-Yu; Tseng, Ming-Chun; Lien, Shui-Yang; Zhu, Wen-Zhang
Abstract: Indium tin oxide (ITO) film was prepared by an in-line magnetron sputtering system equipped with a high power impulse power source. The influences of working pressure on the film deposition mechanism and properties were investigated. The excitation/ionization level of the sputtered species increases with working pressure as indicated by optical emission spectra. The Sn/In atomic ratio and oxygen vacancy concentration in the film decreases as working pressure increases due to unequally increasing ionization rate and self-sputtering yield of Sn and In atoms and stronger oxidizing activity of oxygen species. As a result, The film resistivity, transparency and optical band gap increase with working pressure. ITO film with a low resistivity of 3.7 × 10 −3 Ω cm and a high transmittance at 380–800 nm of over 84.7% can be obtained when deposited at a working pressure of 8 × 10 −2 Torr. Highlights: ∙ Indium tin oxide (ITO) film was prepared by an in-line high power impulse magnetron sputtering system with a moderate deposition rate of 13 nm/min. ∙The influences of working pressure on the deposition mechanism and properties of the HiPIMS-ITO film were investigated. ∙It was found that the Sn/In composition and the opto-electronic properties of ITO film can be tuned by the working pressure. ∙ITO film with a low resistivity of 3.7 × 10 −3 Ω cm and transmittance in the visible/infrared light range (380–800 nm) of over 84.7% was obtained by HiPIMS at a working pressure of 8 × 10 −2 Torr.